Review of audience gratification with Chinese online film festivals - Yang, Yening; Ahmad Ghazali, Akmar Hayati; Shari, Sharil Nizam (Redfame Publishing, 2024)
After COVID-19, cultural activities increasingly rely on online formats to engage audiences. Against this backdrop, online film festivals have emerged as a new subject of film festival research. The proliferation of online film festivals in China during this time has sparked intense debate, with both their emergence and future development being contentious issues. Throughout this process, the will of the audience plays a pivotal role in shaping their trajectory. To ensure the smooth operation and future development of online film festivals, a profound understanding of festival audiences needs to be sought. This study focuses on the audience, aiming to explore their gratification with Chinese online film festivals through a literature review, with the hope of providing insights for future prospects in the planning of online film festivals. Through the screening of databases including CNKI, Google Scholar, and Scopus, a total of 1,352 relevant articles were retrieved. After manual screening and exclusion by researchers, 105 articles relevant to the theme of this study were identified. Based on these articles, this paper synthesizes four types of audience gratification: content gratification, process gratification, social gratification, and technology gratification. Future research is recommended to further empirically investigate the conclusions drawn from this review.